Aircraft Propulsion and Gas Turbine Engines, Second Edition. - El-Sayed, Ahmed F. (Chapman and Hall/CRC, 2017)
Aircraft Propulsion and Gas Turbine Engines, Second Edition builds upon the success of the books first edition, with the addition of three major topic areas: Piston Engines with integrated propeller coverage; Pump Technologies; and Rocket Propulsion. The rocket propulsion section extends the texts coverage so that both Aerospace and Aeronautical topics can be studied and compared. Numerous updates have been made to reflect the latest advances in turbine engines, fuels, and combustion. The text is now divided into three parts, the first two devoted to air breathing engines, and the third covering non-air breathing or rocket engines.